(untitled) (Research, Society and Development, 2022)
Objective: To verify the contributions of the academic tutoring activities developed by PET Nursing, aimed at welcoming, monitoring and guiding the freshmen, as well as assisting in the integration of the academic, scientific and cultural activities of the course and the university. Methodology: This is a cross-sectional research with a quantitative approach, developed in a public higher education institution, located in the state of Ceará. Results: However, the continuity of the sample in the undergraduate course is highlighted, especially among those who have experienced the academic tutoring and the positive evaluation of the participating students, who recognize the influence of the activity on their academic trajectory, as well as demonstrate satisfied with the topics covered and recommend the experience of tutoring. Conclusion: Achieving, in this way, the objectives established by the researchers of contributing to academic development, stimulating and raising awareness among newcomers to gradually sketch the life and career paths they want to build.